Identifikasi Determinan Faktor Risiko Yang Mempengaruhi Pengendalian Hipertensi Di Wilayah Kerja Puskesmas Rasau Jaya - Naya Avilia; Dedi Alamsyah; Andri Dwi Hernawan (Jurnal Ilmiah Manusia Dan Kesehatan, 2026)
Hypertension is classified as a group of non-communicable diseases with a high incidence and serious consequences for population health. This study aims to determine the relationship between medication adherence, family history, and knowledge levels with hypertension control in the Rasau Jaya Community Health Center work area. The type of research used was quantitative with an observational analytical design with a cross-sectional approach. The sample used was 252 hypertension patients using a purposive sampling method. The statistical test used was the chi-square test to determine whether there was a relationship between medication adherence, family history, and knowledge with the incidence of hypertension. From the results of this study, there was a relationship between medication adherence (p < 0.014) and family history (p < 0.000) with hypertension control. And knowledge was not related to hypertension control (p > 0.119). The conclusion of this study is that there is a relationship between medication adherence and family history, while knowledge is not related to hypertension control.